O uso da metacognição na atividade docente: uma trilha fértil na formação de professores para o ensino à diversidade - Bavaresco, Márcia Regina Cordeiro (2010)
This work verified if the use of metacognition helped the improvement of the professional performance of a teacher from Regular Study for the diversity teaching. The theoretical choices were based on the Vygotskys´s psychological theory and on metacognition studies. An intervention study of a case was done methodological, using varied sources and instruments as: a selection of a teacher to participate of the study of a case; characterization of the school and what is around it; a collect of o take her way of being, think and feel; to apply on students a activities observation. These instruments collected data that were used to plan and apply a practice and theoretical formation model for the use of metacognition through three situations always with or without the researcher help: 1st) the Portuguese class planning; 2nd) the class applying with a video register; 3rd) a monitoring, done by the teacher, of her own teaching activity by watching the video class. The chosen case was of a teacher from a municipal public school in a city in Santa Catarina, indicated by the school director, because of her persistency of continuing teaching in the third grade of Elementary School. The same group, of fifteen children, have already been her students one year before, in despite to problems they have had. To get the professional movement in her teaching activity were undertaken a variety of analysis, among them; the signification nucleus and the results of the diagnostic evaluation of as well the subjects that were emerging from what was observed in her class. All of these offered hints to developed a model of formation that considered what the teacher considered as been the ideal, with information and discussions of theoretical nature (N=3) and practice (N=4), all of them articulated in order to lead the teacher regulate her teaching activities, at the beginning with the researcher help, and later alone. The results of this study showed being possible to improve the performance when using the metacognitives process; through a work that got her rid of her isolation, giving her help to perceive a great number of possibilities of her students and planning, carrying out and monitoring the accomplished activities, with the aim of leading the group to appropriate themselves of the school knowledge. As the investigated teacher there are a great number of teachers equally lonely that need not only to divide their anguishes, but - also- and above of all change experiences, face conceptions, identify problems and get solutions. This contribution can be done in and for the school, between the professionals that act in there, promoting, through dialogue, the conscience of how theory directs the pedagogical practice, and how this last one gives new theoretical questions. The use of metacognition in formative strategies represents a fruitful way for teachers´s formation, giving them capacity to accomplish a good quality work, aiming the success for all of the students, effectively, a goal of a teaching with the focus on the diversity